GNSS over-the-air testing using wave field synthesis - Rügamer, Alexander; Del Galdo, Giovanni; Mahr, Johannes; Rohmer, Günter; Siegert, Gregor; Landmann, Markus (26th International Technical Meeting of the Satellite Division of the Institute of Navigation, ION GNSS 2013, 2013)
This paper presents an over-the-air (OTA) wave field synthesis (WFS) system for test and certification of GNSS receivers. We discuss its application with respect to jammers, spoofers and classified signals and compare it to the state-of-the-art in GNSS receiver testing. Having outlined the OTA WFS system architecture, different test cases are described. We verify the emulated OTA environment on one selected test case in an experiment emulating a realistic GNSS signal and artificial jammers, while employing a 2×2 GNSS array antenna with a 4 channel receiver as device under test. The results in terms of direction of arrival estimation and jammer mitigation are finally presented to proof the concept and feasibility of the multi-directional over-the-air testbed. Moreover these results show the need for accurate jammer propagation modelling.
CRIS-Team Scopus Importer:2025-11-10